Shaped-Pattern Reflectarray Antennas for mm-Wave Networks Using a Simple Cell Topology - Borja Imaz-Lueje; Alvaro F. Vaquero; Daniel R. Prado; Marcos R. Pino; Manuel Arrebola (IEEE Access)
In this paper, it is proposed the use of ultra-thin reflectarrays in some emerging scenarios in the new mm-wave cellular networks such as 5G, Beyond-5G (B5G), and future 6G. To that purpose, two dual-linear polarization reflectarrays are developed to provide coverages in different scenarios at the mm-waves band. Working at 28 GHz, reflectarray designs adapt the radiated field to the coverage area specified in each scenario, through an ultra-thin surface composed of simple cells. To evaluate the antenna performance, two reflectarray prototypes identical in size are manufactured and tested achieving a good trade-off between the performance and the low-cost, low losses and, low-profile characteristics of the antenna. This work demonstrates the good performance of simple topology reflectarrays, being an interesting antenna candidate in the upcoming wireless networks.